2021
DOI: 10.1002/smtd.202100758
|View full text |Cite
|
Sign up to set email alerts
|

3D MOF Nanoarchitecture Membrane via Ultrafast Laser Nanoforging

Abstract: Metal‐organic framework (MOF) crystals are useful in a vast area of applications because of their unique chemical and physical properties. Manufacturing of an integrated MOF membrane with 3D nanoarchitectures on the surface is especially important for their applications. However, as MOF crystals usually exist as powdery crystals, fabrication of their large area, monolithic, and high‐resolution patterns is challenging. Here, it is found that isolated MOF nanocrystals could be directly converted to a monolithic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Due to these properties, transition-metal ditellurides have found diverse applications in fields such as optoelectronics, catalysis, and energy conversion. 29,30 The unique features of these materials, including a Dirac cone structure similar to that of graphene, high carrier mobility, and a wide operating band, distinguish them from conventional TMDCs. 20,31 As a result, they hold immense potential for applications in ultrafast pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these properties, transition-metal ditellurides have found diverse applications in fields such as optoelectronics, catalysis, and energy conversion. 29,30 The unique features of these materials, including a Dirac cone structure similar to that of graphene, high carrier mobility, and a wide operating band, distinguish them from conventional TMDCs. 20,31 As a result, they hold immense potential for applications in ultrafast pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…[41] However, as the thermal conductivity of cement, especially dried porous cement, is not sufficiently large, there is still much room to improve the PCM composite system here. Liquid metals (LMs) or alloys, normally in the liquid phase at room temperature, offer high thermal conductivity, low toxicity, and fine fluidity, [42,43] when used as filling materials for PCM capsules. In 2020, Yuan et al developed a lightweight GaInSn-based LM composite, [44] in which the liquid-phase LM could fully contact with incorporated glass microbeads, which suggested that PCM capsules/LM composite have great feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] However, as the thermal conductivity of cement, especially dried porous cement, is not sufficiently large, there is still much room to improve the PCM composite system here. Liquid metals (LMs) or alloys, normally in the liquid phase at room temperature, offer high thermal conductivity, low toxicity, and fine fluidity, [ 42,43 ] when used as filling materials for PCM capsules. In 2020, Yuan et al.…”
Section: Introductionmentioning
confidence: 99%